1980
DOI: 10.1111/j.1346-8138.1980.tb01966.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Senile Keratosis

Abstract: Three cases of a hypertrophic type of senile keratosis were examined by an electron microscope. All three showed similar changes, although some variability from case to case was also observed. Lesional epidermis showed widened intercellular spaces with microvilli‐formation, a general increase in the bulk of the basal cells, a decrease in number of desmosomes, a decrease in the amount of tonofilaments, various degrees of aggregations of tonofibrils, binucleated keratinocytes, mitotic figures, prominent nucleoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1982
1982
1982
1982

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Senile keratosis (SK) has been classified as one of the premalignant epidermal tumors usually arising on sun -exposed areas of the aged. Although there have been comprehensive descriptions from the clinico-histopathological standpoint (1)(2)(3)(4)(5)and SK is not infrequently encountered, no ultrastructural studies of SK have been reported to date except for one (6) on a hypertrophic type of SK. In the present study, three cases of SK, all of which were histologically atrophic, were examined by electron microscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Senile keratosis (SK) has been classified as one of the premalignant epidermal tumors usually arising on sun -exposed areas of the aged. Although there have been comprehensive descriptions from the clinico-histopathological standpoint (1)(2)(3)(4)(5)and SK is not infrequently encountered, no ultrastructural studies of SK have been reported to date except for one (6) on a hypertrophic type of SK. In the present study, three cases of SK, all of which were histologically atrophic, were examined by electron microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, three cases of SK, all of which were histologically atrophic, were examined by electron microscopy. The ultrastructural findings were compared with those from a hypertrophic type of SK (6) and from Bowen's disease (7 -10).…”
Section: Introductionmentioning
confidence: 99%